Two new species of the Phimochirus holthuisi complex from the Gulf of Mexico, supported by morphology, color, and genetics (Crustacea: Anomura: Paguridae) - Felder, Darryl L.; Lemaitre, Rafael; Craig, Catherine (Zootaxa, 2019)
Coloration, gene-sequence data (H3, 12s, 16s), and subtle features in morphology support the description of two new species, both formerly regarded to represent accepted variants of Phimochirus holthuisi s.l. While color in life consistently separates these species from P. holthuisi s.s. and from each other, morphological distinctions are subtle and less than absolute in small specimens, being based on ventral spine counts of walking leg dactyls and relative development of the superior crest on the major chela. Molecular phylogenetic analyses clearly support the separation of sister clades, representing two new species, from P. holthuisi s.s. as well as other congeners available for analysis. Both of the new species are presently known to occur widely throughout the northern Gulf of Mexico, though one occurs more commonly in the northeastern and southeastern Gulf, and may range as far south as Suriname. The other has been taken primarily in the northwestern Gulf, and is not known from outside Gulf waters. While both of the new species appear restricted to relatively deep subtidal waters of the continental shelf, Phimochirus holthuisi s.s. is instead more commonly found in shallow nearshore tropical waters on or near coral reefs. Previous literature reports of P. holthuisi usually represent, at least in part, one or both of these two new species.